2015
DOI: 10.4103/1319-2442.164578
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis versus peritoneal dialysis, which is cost-effective?

Abstract: There is an increasing need for renal replacement therapy due to the growing number of cases with chronic kidney disease leading to end-stage renal disease. Two modalities of dialysis available are hemodialysis (HD) and peritoneal dialysis (PD). In this study, we aimed to compare the financial aspects of HD with PD. A total of 53 patients on HD and 43 patients on PD were included in the study and were assessed for several financial aspects of dialysis. The data collected were analyzed using SPSS-18. A statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…A pesar de que en muchos países del tercer mundo la DP ha sido sugerida como la TRR más económica y ha sido impulsada en Perú [20,37,38]. En el análisis económico, esta ha resultado más cara comparada con la HD [7,20].…”
Section: Terapias De Reemplazo Renalunclassified
“…A pesar de que en muchos países del tercer mundo la DP ha sido sugerida como la TRR más económica y ha sido impulsada en Perú [20,37,38]. En el análisis económico, esta ha resultado más cara comparada con la HD [7,20].…”
Section: Terapias De Reemplazo Renalunclassified
“…Berger et al [3] reported a two times higher likelihood of hospitalization in the first 12 months after initiation of HD as opposed to PD, with median healthcare costs higher by $43,510 for HD. Atapour et al [9] likewise found a statistically significant difference between HD and PD in terms of factors such as diagnostic tests, drugs, and hospitalization, with higher costs for HD.…”
Section: Discussionmentioning
confidence: 95%
“…Among dialysis, hemodiafiltration, a form of HD, is considered as a cost-effective therapeutic option 22 . In contrast to HD, PD stood out as a lower cost option 10,19 . In Spain, HD is five times more expensive than the treatment of the more advanced stages of CKD and three times more expensive than transplantat 33 .…”
Section: Methodsmentioning
confidence: 99%